Analysis of the pink narrative of female creators and artists of audiovisual fiction: Barbie and Super Freaky Girl - Martínez Cano, Silvia; Meléndez Táboas, Amelia; Alonso Martín-Romo, Luis (Historia y Comunicación Social, 2024)
This paper analyses by contrast the narratives of empowerment in two mainstream productions, the film Barbie (Gerwig, 2023) and the music video Super freaky girl (Minaj, 2022). From a visual, aesthetic and linguistic analysis of the two productions, the emergence of a new "pink" in the most representative female audiovisual creators of recent years is explored in depth. Starting from the question of the relationship between body stereotypes, femininity and the empowerment of women in the audiovisual narrative, we will point out the frictions between the construction of gender in the structures of power. In practice and theory these productions under the absolute control of their creators reveal a paradigm of the new visually excessive "pink" through sorority in one case (Barbie) and competitive hypersexualisation in the other (Minaj).